2013
DOI: 10.1126/science.1244324
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Mediated Interactions Between Distant Artificial Atoms

Abstract: Photon-mediated interactions between atoms are of fundamental importance in quantum optics, quantum simulations, and quantum information processing. The exchange of real and virtual photons between atoms gives rise to nontrivial interactions, the strength of which decreases rapidly with distance in three dimensions. Here, we use two superconducting qubits in an open one-dimensional transmission line to study much stronger photon-mediated interactions. Making use of the possibility to tune these qubits by more … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
469
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 528 publications
(494 citation statements)
references
References 30 publications
14
469
0
2
Order By: Relevance
“…While this Review has described some applications that utilize the high Q, there are many more opportunities such as in nonlinearity enhancement and in quantum optical applications that have not been explored. The long-range interactions in FabryPérot BICs may be useful for nanophotonic circuits 104 and for quantum information processing 105,106 . It has also been proposed that the light intensity may act as another tuning parameter in nonlinear materials, which may enable robust BICs 248 , tunable channel dropping 249 , light storage and release 250,251 , and frequency comb generation 252 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this Review has described some applications that utilize the high Q, there are many more opportunities such as in nonlinearity enhancement and in quantum optical applications that have not been explored. The long-range interactions in FabryPérot BICs may be useful for nanophotonic circuits 104 and for quantum information processing 105,106 . It has also been proposed that the light intensity may act as another tuning parameter in nonlinear materials, which may enable robust BICs 248 , tunable channel dropping 249 , light storage and release 250,251 , and frequency comb generation 252 .…”
Section: Discussionmentioning
confidence: 99%
“…Such long-range interactions have been studied in cavities or qubits coupled through a waveguide [104][105][106] and for two leaky solitons coupled through free-space radiation 107 .…”
Section: Fabry-pérot Bic (Through Coupled Resonances)mentioning
confidence: 99%
“…The fit yields an extinction 1 − T min ≈ 0.87 AE 0.17 for the bare TMD monolayer. We emphasize that extinction factors of this magnitude were previously only reported for transmon qubits coupled to superconducting microwave waveguides [22].…”
mentioning
confidence: 96%
“…For this phenomenon he coined the term superradiance and showed that the atom ensemble can behave as a large collective pseudospin. Superradiant emission has been observed in numerous physical systems [2][3][4][5][6][7][8][9][10]. These collective effects are particularly prominent when the coupling between the spin ensemble and the radiation field (g ffiffiffiffi N p for N spins individually coupled with strength g) is larger than any of the losses in the system (κ þ γ, where κ is the radiative loss rate and γ is the spin dephasing rate).…”
mentioning
confidence: 99%